If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -4 + 2x + 10 = 0 Reorder the terms: -4 + 10 + 4x + 2x = 0 Combine like terms: -4 + 10 = 6 6 + 4x + 2x = 0 Combine like terms: 4x + 2x = 6x 6 + 6x = 0 Solving 6 + 6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 6x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 6x = 0 + -6 6x = 0 + -6 Combine like terms: 0 + -6 = -6 6x = -6 Divide each side by '6'. x = -1 Simplifying x = -1
| 15(-8*0.7+244)= | | 3x+(4x+9)=-12 | | 15(-42*0.7+40)= | | rt=rk | | (4/x)+2-(3/2)=0 | | -255=3x-7(3x+21) | | 63-4x=5x+19 | | y^2+14y-15=0 | | 18h=63 | | 4(-7k-7)=84 | | 74-5x=4x+23 | | 4q^2+3q=3q^2-4g+18 | | (-42*-6+40)=15(-8*-6+244) | | -7x-1(-2x-2)=27 | | 123=-7x+5(5x-15) | | (15/8)z+(1/4)-4 | | 2y^2-7y-13=-10 | | (-42x+40)=15(-8x+244) | | (-42+40)=15(-8x+244) | | -281=-6x+7(-3x-17) | | 5(7-2y)+9y=31 | | (3R/4)-(4/5)=(7/10) | | 15=4x-7(x-6) | | 18-(14+f)=1-(4f+6) | | 6x+5(-5x+13)=-68 | | -2-6x=4x+12 | | -260=-3x-5(-6+25) | | 15x+20=5x+200 | | 10-x-x=24 | | 6(2c-7)+16=2(4c-1)+8 | | 8*4n-1= | | -68=-4x+5(-x-8) |